Democracy, Economic Growth and Global Carbon Dioxide Emission - Islam, Mohammad Kamrul (Université d'Ottawa | University of Ottawa, 2016)
The transmission process of the influence of a political institution on the environment-income nexus is multi-faceted and complex. We use panel data set on 147 countries for 23 years to investigate empirically the role democracy plays in the income-pollution nexus. Environmental interest groups can promote more awareness in the presence of democracy. Democratic governments are more responsive to the public than are non-democratic governments. Accumulation of civic and social right generated through historical experience is important in maintaining stable and responsive environmental policy. The finding of this paper is that not only the level of democracy but also the consistency in countries’ political institution (whether a country maintains a steady score in freedom indicator) is influential in defining the tipping point of environmental Kuznets Curve.